Il futuro è urbano - Callari Galli, Matilde (Scienze del Territorio, 2015)
As opposed to an approach that stresses the consequences of urbanisation in terms of increasing insecurity, localism, violence, the author proposes a positive and action-oriented attitude, illustrated by a recent experience initiated by the City Council of Bologna. From the empirical observation of the existence of a new poverty linked with precarious work, even in a traditionally wealthy city, springs the ‘Zanardi houses’ project (‘case Zanardi’), that aims to promote new forms of mutual help and sharing, to counter individualism and strengthen the city’s social capital.